2005
DOI: 10.1111/j.1537-2995.2005.00610.x
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of hematologic patients to parvovirus B19 as a contaminant of blood cell preparations and blood products

Abstract: Although B19 DNA was detected in 1 percent of blood products given to hematologic patients, the exposure of 12 percent of patients did not result in symptomatic infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
43
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 44 publications
(84 reference statements)
2
43
0
Order By: Relevance
“…Although, this seems quite reassuring, these results cannot be generalized as they represent testing of small batches and continuous monitoring is recommended. Other researchers from different countries have been able to detect parvovirus B19 DNA in 1 percent of all blood cell preparations and blood products applied to the patients on a haematologic ward, in 0.9 percent of standard blood components (in 2.0 percent of pooled plasma products and in 0.7 percent of single donor products), 18 in 0.006 percent of blood donations, in 0.14 percent of single-donor blood products, 19 in 0.16 percent of plasma samples, 15 in 0.6e1.3 percent of blood donors. 13 Given these data, it is apt that screening of blood donors for parvovirus B19 is now in prospect.…”
Section: Discussionmentioning
confidence: 99%
“…Although, this seems quite reassuring, these results cannot be generalized as they represent testing of small batches and continuous monitoring is recommended. Other researchers from different countries have been able to detect parvovirus B19 DNA in 1 percent of all blood cell preparations and blood products applied to the patients on a haematologic ward, in 0.9 percent of standard blood components (in 2.0 percent of pooled plasma products and in 0.7 percent of single donor products), 18 in 0.006 percent of blood donations, in 0.14 percent of single-donor blood products, 19 in 0.16 percent of plasma samples, 15 in 0.6e1.3 percent of blood donors. 13 Given these data, it is apt that screening of blood donors for parvovirus B19 is now in prospect.…”
Section: Discussionmentioning
confidence: 99%
“…18 In contrast, 2 studies have reported a small number of negative results when patients transfused with B19V DNA-positive components were evaluated for laboratory markers of B19V infection. 19,20 Nevertheless, given the tropism for 21 and potential pathophysiologic effects of B19V infection on erythroid precursor cells, 22 concern remains for potential deleterious outcomes in frequently transfused hematology patients with underlying hemolysis or compromised erythropoiesis syndromes. 13 Because the sensitivity of B19V DNA assays has improved, B19V DNA prevalence in blood donors has been shown to be An Inside Blood analysis of this article appears at the front of this issue.…”
mentioning
confidence: 99%
“…In a study conducted in an adult hematology service, 6 adult recipients with hematologic malignancies (5 of whom underwent stem cell transplantation) were identified as transfused with blood components that were retrospectively found to contain B19V DNA at less than 10 6 geq/ mL; in 4 of 5 evaluated cases, the DNA-positive component also contained B19V IgG. Each recipient was B19V DNA negative when tested 3 to 18 days after transfusion, 19 and none showed clinical symptoms of B19V infection on retrospective chart review. 19 The mechanism to explain lack of transmission to susceptible recipients by B19V DNA-containing units is unknown but could be related to the lack of a large enough inoculating dose of B19 virions to establish infection.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence for parvovirus B19 transmission via blood products, PBSC or bone marrow. 4,5 Patients required erythrocyte infusions during conditioning before trans-plantation. Parvovirus B19 is known to be a frequent contaminant of blood products, 6 but as parvovirus B19 screening is not part of the routine control of blood products in Germany it was not analysed, and so infection via this route cannot be excluded.…”
mentioning
confidence: 99%